Multi-stage silicon-carbon composite material for battery negative electrode and preparation method of multi-stage silicon-carbon composite material

By preparing Si@C/CNFs anode materials through ball milling and electrospinning, the problems of complex preparation and high cost in existing technologies have been solved, and high-capacity, long-life silicon-carbon composite materials have been achieved, thus improving the electrochemical performance of lithium-ion batteries.

CN121035140APending Publication Date: 2025-11-28TIANJIN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410661375.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing technologies for preparing silicon-carbon composite anode materials suffer from drawbacks such as the use of toxic and harmful raw materials, numerous and complex operations, inability to mass-produce, and high costs. Furthermore, silicon-based anode materials face structural damage, cycle stability, and conductivity issues due to volume expansion in lithium-ion batteries.

Method used

By employing ball milling and electrospinning techniques, uniform mixing of materials is achieved through ball milling, and a carbon nanofiber network is constructed by electrospinning. Using polymer PAN as the carbon source, Si@C/CNFs anode materials are prepared, forming an N-doped carbon coating and strong Si-OC chemical bonds, thereby improving structural stability and conductivity.

Benefits of technology

Excellent cycle stability and rate performance were achieved, and high-capacity, long-life silicon-carbon composite materials were prepared, simplifying the production process, reducing costs, and improving the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121035140A_ABST
    Figure CN121035140A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of lithium ion battery negative electrode materials, and particularly relates to a multi-stage silicon-carbon composite material for a battery negative electrode and a preparation method of the multi-stage silicon-carbon composite material. The method comprises the following steps: firstly, weighing DMF, Si NPs and PAN, carrying out ball milling, and then carbonizing in an N2 atmosphere to obtain a Si-C primary structure of a target sample; then uniformly dispersing Si-coated C and PAN in a DMF (Dimethyl Formamide) solution to obtain an electrostatic spinning working solution, and then preparing a Si-coated C composite PAN nanofiber membrane Si-coated C / PAN under an optimal electrostatic spinning working condition; and finally, stabilizing the fiber structure of the Si-coated C / PAN in the air, and carbonizing in the N2 atmosphere to obtain the multistage silicon-carbon composite material Si-coated C / CNFs for the battery negative electrode prepared by electrostatic spinning. According to the invention, an amorphous carbon layer is compounded on the surface of Si NPs by a ball milling method, and a carbon nanofiber network is built in combination with electrostatic spinning, so that the Si NPs are subjected to double constraints of amorphous carbon and carbon nanofibers. And the prepared silicon-carbon composite negative electrode material shows excellent cycling stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of lithium ion battery negative electrode material preparation, and particularly relates to a multi-stage silicon-carbon composite material for a battery negative electrode and a preparation method thereof. BACKGROUND

[0002] With the improvement of environmental awareness, lithium ion batteries have a wide range of application requirements in the fields of electric vehicles, portable electronic devices, energy storage, aerospace, etc., and with the progress of technology and the continuous expansion of application fields, the demand will continue to grow. As an important component of the negative electrode material, achieving higher energy density, longer cycle life, higher safety and lower cost has become our goal. Among them, Si as a lithium ion battery negative electrode material has a theoretical specific capacity of 4200mAh g -1 , about 10 times (370mAh g –1 ) of the current mainstream graphite negative electrode. Therefore, silicon-based negative electrode materials are a very promising lithium ion battery negative electrode material and are attracting attention. First, silicon has a high theoretical specific capacity, which means that silicon-based negative electrode materials can store more lithium ions, achieving higher battery energy density, thereby providing longer battery life and higher power output. At the same time, the lithium insertion potential of silicon is moderate (0.4V vs. Li 0 / Li + ), with less risk of lithium dendrite formation, thus having good safety. Secondly, silicon is one of the most abundant resources on earth, relatively easy to obtain, which is conducive to reducing battery production costs, and compared with some rare metals, silicon is a more environmentally friendly and sustainable material, which helps to reduce dependence on limited resources and meets the requirements of sustainable development. However, it also faces some challenges, such as structural damage caused by volume expansion, cycle stability and conductivity. Despite this, lithium ion battery silicon-based composite negative electrode materials are still an important way to improve battery energy density, and further research and technological breakthroughs are needed to solve the challenges it faces. SUMMARY

[0003] The purpose of the present application is to overcome the defects of using toxic and harmful raw materials, complicated operation, inability to mass production and high cost in the preparation of silicon-carbon composite negative electrode materials by the existing method, and to provide a silicon-carbon composite negative electrode material prepared by ball milling and electrospinning and a preparation method thereof. The present application utilizes the feature of uniform mixing of materials by ball milling, combined with the construction of carbon nanofiber network by electrospinning, uses commonly used polymer PAN as carbon source to prepare silicon-carbon composite negative electrode material, and realizes excellent cycle stability and rate performance in electrochemical test.

[0004] In order to achieve the above object, the application provides a preparation method of a multi-stage silicon-carbon composite material for a battery negative electrode, comprising the following steps:

[0005] S1, N,N-dimethylformamide (DMF), silicon nanoparticles (Si NPs) and polyacrylonitrile (PAN) are weighed and added to a marver jar for ball milling to obtain a PAN-coated Si NPs composite (Si@PAN); and then carbonization under a N2 atmosphere to obtain a target sample Si@C primary structure;

[0006] S2, Si@C and PAN are uniformly dispersed in a DMF solution, and after vigorous stirring, a uniformly dispersed electrospinning working solution is obtained to obtain an electrospinning working solution;

[0007] S3, under the optimal electrospinning working conditions, Si@C / PAN nanofiber membranes are prepared;

[0008] S4, after the Si@C / PAN nanofiber membranes are stabilized in air, carbonization under a nitrogen atmosphere is performed to obtain Si@C / CNFs

[0009] According to the application, in the electrospinning preparation method of the multi-stage silicon-carbon composite material for a battery negative electrode, the use of ball milling to mix Si NPs and PAN precursors is combined, so that the Si@C / CNFs negative electrode has an N-doped carbon coating layer and a firm Si-O-C chemical bond at the interface. A firm chemical bond is formed between Si and C, thereby improving the structural stability of the Si@C composite material during lithium storage. The carbon nanofiber network is considered to be an essential element for preventing the aggregation and fracture of silicon nanoparticles during lithiation / delithiation. Abundant conductive contacts are beneficial to Li + and electron diffusion kinetics.

[0010] According to the application, in the electrospinning preparation of the multi-stage silicon-carbon composite material for a battery negative electrode, a small amount of N element is doped, the N element doping improves the conductivity and electron mobility of the negative electrode material by introducing additional electron donors or acceptors, increases the number of active sites, and enhances the insertion and de-insertion kinetics of lithium ions. The N element doping is confirmed by X-ray photoelectron spectroscopy.

[0011] Further, in step S1, the weight ratio of Si NPs to PAN is 1:5.

[0012] Further, the particle size of the silicon nanoparticles (Si NPs) is 100-200 nm, the ratio of balls to materials during ball milling is 20:1, the ball milling rotation speed is 500-700 rpm, and the ball milling time is 10-12 h.

[0013] Further, in step S1, the carbon source used can be polyacrylonitrile (PAN), polyvinylpyrrolidone (PVP), polyethylene glycol (PEG) and the like polymer powder having long carbon chain, preferably PAN and PVP, more preferably PAN powder.

[0014] Further, in step S1, the inert gas used in the carbonization process of PAN-coated silicon nanoparticles can be N2 and Ar, preferably N2. The carbonization temperature is 700-900℃, and the carbonization time is 2-4h.

[0015] Further, in step S2, the stirring temperature for preparing the uniformly dispersed electrospinning working solution is 50-80℃, more preferably 60℃, and the stirring time is 8-12h.

[0016] Further, in step S3, the flow rate of the electrospinning injection working solution is 0.1-1ml h -1 , the distance between the needle tip and the metal plate is 10-15cm, and the applied voltage is 15-20kV, more preferably, the flow rate is 0.3ml h -1 , the distance is 15cm, and the voltage is 16kV.

[0017] Further, in step S4, the stabilization process is carried out in a muffle furnace, the muffle furnace heating temperature is 220-280℃, the heating time is 2-4h, and the heating rate is 2-5℃·min -1 .

[0018] Further, in step S4, the carbonization process is carried out in a tube furnace, the tube furnace heating temperature is 800-1000℃, the heating time is 1.5-3h, and the heating rate is 2-5℃·min -1 .

[0019] The second aspect of the present application provides a multi-stage silicon-carbon composite material for battery negative electrode prepared by the above method, comprising amorphous carbon-coated silicon nanoparticle primary structure, the average particle size is 0.1-1μm, and the carbon-coated silicon nanoparticle coated or combined with carbon nanofiber, the average fiber diameter is 0.2-1.5μm.

[0020] The present application has the following beneficial effects:

[0021] 1) The excellent electrical conductivity of the Si@C primary nanostructure plays an important role in the electrode performance. This primary structure is synthesized by ball milling and has excellent electrical conductivity. Combined with the constraint of the carbon matrix, the volume expansion of the silicon nanoparticles is delayed, and their aggregation is improved, thereby maintaining the integrity of the electrode.

[0022] 2) The electrospinning process of the present invention ensures the optimum silicon content in the composite material by adjusting the diameter of the carbon nanofiber, reducing the electrospinning voltage, increasing the solution concentration, reducing the injection speed and using a larger diameter needle, etc., reducing the exposure of silicon nanoparticles on the surface of the fiber, thereby improving the electrochemical performance.

[0023] 3) The carbon nanofiber network also plays a key role in the structure of the Si@C / CNFs electrode material. The carbon nanofiber network prevents the aggregation and fracture of the silicon nanoparticles during the lithiation / delithiation process, and the abundant conductive contact facilitates Li + and electron diffusion kinetics, improving the original single-point contact mode of the silicon nanoparticles.

[0024] 4) The present invention uses a ball milling method to coat an amorphous carbon layer on the surface of the silicon nanoparticles, combined with a simple electrospinning method to build a carbon nanofiber network, to prepare an advanced negative electrode material with high capacity and long life. The use of ball-mixed Si NPs and PAN precursors in combination with the electrospinning method to build a carbon nanofiber network makes the negative electrode have a N-doped carbon coating, thus showing enhanced electrical conductivity, excellent rate performance and outstanding structural durability during cycling. The electrode shows excellent electrochemical performance at a specific capacity density of 0.1 and 1 Ag -1 , respectively, at the 100th and 500th cycles, with a specific capacity of 963.5 and 652.5 mAh g -1 , respectively. The simple scalable preparation method and excellent electrochemical performance provide a strong guarantee for the electrode to be used in advanced lithium-ion battery anodes. BRIEF DESCRIPTION OF DRAWINGS

[0025] Figure 1 A flow chart of the preparation of the multi-stage silicon-carbon composite material for the battery negative electrode prepared by electrospinning according to the present invention.

[0026] Figure 2 X-ray diffraction patterns of the negative electrode materials prepared in Examples 1 and 2 of the present invention.

[0027] Figure 3 Raman spectra of the negative electrode materials prepared in Examples 1 and 2 of the present invention.

[0028] Figure 4 X-ray photoelectron spectroscopy of the negative electrode materials prepared in Examples 1 and 2 of the present invention.

[0029] Figure 5 Scanning electron micrographs of the negative electrode materials prepared in Examples 1 and 2 of the present invention.

[0030] Figure 6 Transmission electron micrographs of the negative electrode materials prepared in Examples 1 and 2 of the present invention.

[0031] Figure 7 Galvanostatic charge-discharge curves of the negative electrode material prepared in Example 1 and 2 of the present application.

[0032] Figure 8 Cycle performance chart of the negative electrode material prepared in Example 1, 2 and Comparative Example 1 of the present application at 0.1 Ag -1 current density.

[0033] Figure 9 Long cycle performance chart of the negative electrode material prepared in Example 1 and 2 of the present application at 1 Ag -1 current density.

[0034] Figure 10 Rate performance chart of the negative electrode material prepared in Example 1 and 2 of the present application. DETAILED DESCRIPTION

[0035] In order to make the technical solutions and advantages of the present application clearer, the present application and its beneficial effects will be described in further detail below with reference to specific embodiments and the accompanying drawings of the specification, but the embodiments of the present application are not limited thereto.

[0036] Example 1

[0037] The present embodiment provides a preparation method of electrospinning for preparing a multi-stage silicon-carbon composite material for battery negative electrode, comprising the following steps:

[0038] S1, weigh 2 mL of DMF, 0.2 g of Si NPs and 1.0 g of PAN into a maroon ball mill jar, and ball mill at a speed of 600 rpm for 10 h to obtain Si@PAN composite material, dry the obtained Si@PAN precursor at 70℃, and then carbonize at 800℃ under N2 atmosphere for 3 h with a heating rate of 3℃ min-1 to obtain the target sample Si@C

[0039] S2, disperse 0.3 g of Si@C precursor in a solution containing 5 mL of DMF and 0.58 g of PAN. The obtained mixture is magnetically stirred at 60℃ for 8 hours to obtain a uniformly dispersed electrospinning working solution;

[0040] S3, then transfer the solution to a 10 mL plastic syringe equipped with a flat needle. Under the optimal electrospinning conditions, the syringe is skillfully connected to a single-channel injection pump to ensure that the flow rate is accurately controlled at 0.3 ml h -1 . A grounded metal plate is used as a collector 15 cm below the needle tip, and a voltage of 16 kV is applied between the needle tip and the grounded metal plate to generate a Si@C / PAN nanofiber membrane;

[0041] S4, the Si@C / PAN nanofiber membrane was subjected to a key stabilization process, which was placed in air at 260℃ for 4h continuously, with a heating rate of 5℃ / min -1 After the stabilization process was completed in air, the nanofiber membrane was transferred to a N2 atmosphere for additional heat treatment. The temperature was quickly raised to 900℃ and maintained for 3h, with the same heating rate as the initial stabilization stage, which was set to 5℃ / min -1 . After the nanofiber membrane was naturally cooled to room temperature, a unique Si@C / CNFs structure was formed.

[0042] Example Two

[0043] Based on Example One, the electrospinning steps S2-S4 were deleted, and the other preparation steps were the same as Example One, which was marked as Si@C. In Example Two, the assembly operation of the negative electrode material was the same as Example One.

[0044] Comparative Example One

[0045] This example provides a method for preparing carbon nanofibers, which is different from Example One in that step S1 is deleted, and in step S2, 0.58g of PAN is dispersed in a solution of 5mL of DMF. The resulting mixture is magnetically stirred at 60℃ for 8 hours to obtain a uniformly dispersed electrospinning working solution. Subsequently, the operation steps of S3 and S4 are the same.

[0046] The negative electrode material obtained in Comparative Example One is marked as CNFs. In this comparative example, the assembly operation of the negative electrode material is the same as Example One.

[0047] Specific Application Example One

[0048] In this example, the operation steps for assembling the negative electrode material into a button-type half-cell are as follows: it must be ensured that the operation is carried out in a glove box filled with nitrogen, and the H2O and O2 contents in the glove box must be maintained below 0.1ppm. The battery shell, gasket, and reed used must be cleaned with anhydrous ethanol before entering the glove box, and dried in a vacuum drying oven at 80℃ for more than 7 days. During assembly, the positive electrode shell is placed first, and then the electrode sheet is placed at the center of the positive electrode shell. An appropriate amount of electrolyte is then added, followed by the addition of a separator and an appropriate amount of electrolyte. Then, the metal lithium sheet, gasket, reed, and negative electrode shell are assembled in the order of metal lithium sheet, gasket, reed, and negative electrode shell, ensuring that the placement order of each component during assembly is accurate. Then, the battery is sealed on the battery sealing machine at a pressure of 8MPa. After assembly is completed, the battery is left to stand for more than 12 hours for subsequent electrochemical performance testing.

[0049] The negative electrode materials prepared in Examples One and Two and Comparative Example One were subjected to structure characterization and electrochemical performance testing according to Specific Application Example One, and the experimental results are shown in Figures 2 to 8 .

[0050] FromFigure 2 It can be seen that both Examples 1 and 2 show typical diffraction peaks of crystalline silicon corresponding to (111), (220) and (311) planes of silicon, respectively. No peaks of SiOxwere observed, confirming the amorphous structure of SiOxlayer on the Si surface. A weak peak can be observed at 23.3°, which is attributed to the (002) plane of graphitic carbon x

[0051] From Figure 3 It can be seen that the sharp peaks of Raman spectra appear at 517.3 cm"1, which is related to crystalline Si. The broad peaks of characteristic D and G peaks of carbon appear at 1352 and 1599 cm"1, respectively, confirming the presence of carbon in the composite. -1

[0052] From Figure 4 It can be seen that Example 2 shows diffraction peaks of Si 2s and Si 2p at 153 and 101 eV, respectively, while no such peaks are observed in the sample of Example 1, which is attributed to the increased carbon content leading to increased carbon layer thickness, and thus weakened Si detection signal of XPS. It can also be seen that both Example 1 and Example 2 have nitrogen element doping.

[0053] From Figure 5 It can be seen that the structure of Example 2 is composed of irregular particles, and it can be visually seen that the surface becomes very rough, and there are layered substances present, with sizes ranging from nanoscale to microscale. The thin film of Example 1 has a one-dimensional continuous and uniform nanofiber morphology, with a diameter of about 0.1-1.5 μm. In addition, due to the accumulation of silicon nanoparticles, the fiber surface is abnormally rough. This is because the silicon nanoparticles are anchored and embedded in the fiber, occupying a certain space and leading to a relatively coarse diameter distribution.

[0054] From Figure 6 It can be seen that the dark silicon nanoparticles are embedded in the light carbon matrix, and the FFT image and inverse FFT image corresponding to the innermost layer of crystalline silicon nanoparticles and the outer layer of amorphous carbon coating are observed, and the interplanar spacing of these lattice fringes is 0.31 nm, which is consistent with the (111) plane of cubic phase Si. The results show that Si@C is embedded in the PAN-derived carbon matrix.

[0055] From Figure 7 It can be seen that the first discharge / charge capacity of the electrodes of Example 1 and Example 2 is 1300.6 / 1513.9 mAh g"1 -1 and 1121.4 / 850.6 mAh g"1 -1 , respectively, and the initial coulombic efficiency is 80.6% and 75.9%, respectively. The constant current charge / discharge curve of the electrode of Example 1 shows an overlapping trend after the first cycle, and the CE rises to more than 98% by the third cycle, confirming excellent cycle stability. ​​

[0056] From Figure 8 It can be seen that, at a current density of 0.1 Ag-1, the Example 2 electrode has a higher initial specific discharge capacity due to the higher Si content in the composite material, however, the specific capacity gradually decays with the increase of charge-discharge cycles. After 100 cycles, the specific capacities of the Example 1 and 2 electrodes are 780.8 and 963.9 mAh g-1, respectively, and the capacity retention rates are 48.4% and 86%, respectively. In summary, the Example 1 composite material exhibits better performance than the Example 2 and Comparative Example 1 electrodes.

[0057] From Figure 9 It can be seen that, at a current density of 1 A g-1, the cycle stability of the Example 1 electrode is significantly improved, and the capacity in the 500th cycle is 652.5 mAh g-1, indicating excellent long cycle performance.

[0058] From Figure 10 It can be seen that, when the current density exceeds 0.4 mAg -1 , the Example 1 electrode exhibits higher specific capacity than the Example 2 electrode, especially at higher current densities. Therefore, the Example 1 electrode exhibits excellent rate performance.

[0059] Based on the disclosure and teachings provided herein, a person of ordinary skill in the art will be able to make changes and modifications to the above-described embodiments. Therefore, the present application is not limited to the specific embodiments described above, and any obvious improvements, replacements or modifications made by those skilled in the art based on the present application shall fall within the scope of the present application. In addition, although some specific terms are used in the present specification, these terms are only for convenience of description and do not constitute any limitation on the present application.

Claims

1. A method for preparing a multi-level silicon-carbon composite material for a battery negative electrode, characterized in that, The steps are as follows: S1. DMF, PAN and Si NPs were ball-milled and mixed, and then carbonized at 900℃ for 3h under N2 atmosphere to obtain Si@C; S2. Weigh out Si@C and PAN and disperse them in DMF. After vigorous stirring, a uniformly dispersed electrospinning working solution is obtained. S3. Prepare Si@C / PAN nanofiber membranes under the optimal electrospinning working conditions; S4. After stabilizing the Si@C / PAN nanofiber membrane in air, carbonize it under a nitrogen atmosphere to obtain Si@C / CNFs.

2. The preparation method according to claim 1, characterized in that, In step S1, the particle size of Si NPs is between 100-200 nm.

3. The preparation method according to claim 1, characterized in that, In step S1, the weight ratio of Si NPs to PAN is 1:

5.

4. The preparation method according to claim 1, characterized in that, In step S1, the ball milling speed is 500-700 rpm and the ball milling time is 10-12 h.

5. The preparation method according to claim 1, characterized in that, In step S1, an inert gas is used in the carbonization process.

6. The preparation method according to claim 1, characterized in that, In step S2, the mixture is vigorously stirred at 50–80°C until it is evenly dispersed.

7. The preparation method according to claim 1, characterized in that, In step S3, the flow rate of the electrospinning injection working solution is 0.1–1 ml / h. -1 The distance between the needle tip and the metal plate is 10-15cm, and the applied voltage is 15-20kV.

8. The preparation method according to claim 1, characterized in that, In step S4, the conditions for stabilizing carbon nanofibers in an air atmosphere are: 220–280℃, heating time of 2–4 h, and heating rate of 2–5℃·min. -1 .

9. The preparation method according to claim 1, characterized in that, In step S4, the conditions for carbonizing carbon nanofibers under a nitrogen atmosphere are: 800–1000℃, heating time of 1.5–3 h, and heating rate of 2–5℃·min. -1 .

10. A multi-level silicon-carbon composite material for a battery negative electrode prepared by the method according to any one of claims 1-9, comprising an amorphous carbon-coated silicon nanoparticle primary structure with an average particle size of 0.1-1 μm, wherein the carbon nanofiber-coated or composite carbon-coated silicon nanoparticles have an average fiber diameter of 0.2-1.5 μm.

Citation Information

Patent Citations

  • Silicon-carbon composite material, preparation method thereof and cathode material containing same as well as lithium ion battery

    CN102447112A

  • Preparation method of composite silicon carbon negative electrode material

    CN107394122A

  • Silicon-carbon-polymer composite electrode of lithium secondary battery and preparation method of silicon-carbon-polymer composite electrode

    CN111081976A

  • Self-supporting nitrogen-doped porous carbon-coated silicon nanofiber material for negative electrode of lithium ion battery as well as preparation method and application of self-supporting nitrogen-doped porous carbon-coated silicon nanofiber material

    CN113629251A

  • Preparation method of high-capacity silicon-carbon composite negative electrode material

    CN113725427A